THE LEAN BOOK OF LEAN : A CONCISE GUIDE TO LEAN MANAGEMENT FOR LIFE AND BUSINESS - Earley, John A. A, 1959-
An essential guide to bringing lean to your business and your life The Lean Book of Lean provides a succinct overview of the concepts of Lean, explains them in everyday terms, and shows how the general principles can be applied in any business or person